1992
DOI: 10.1007/bf00844730
|View full text |Cite
|
Sign up to set email alerts
|

The patterning of psychological attributes and distress by ?job strain? and social support in a sample of working men

Abstract: As a test of the "job strain" (job demands-control) model, 297 healthy men aged 30-60 were recruited at eight New York City worksites. The association among job demands and control, social support, and psychological outcomes was tested using both ANCOVA and moderated multiple regression, controlling for demographic variables. The job strain model was supported by various psychological outcome measures, with workers in "active" jobs reporting the highest level of Type A behavior, job involvement, and positive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
77
0
6

Year Published

1994
1994
2003
2003

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(94 citation statements)
references
References 39 publications
11
77
0
6
Order By: Relevance
“…In the context of Karasek and Theorell's (1990) learning hypothesis, the highest levels of commitment/involvement are expected among incumbents of active jobs; the lowest levels are expected for passive jobs. Consistent with the active learning hypothesis, Landsbergis et al (1992) found that levels of job involvement were highest in active jobs. However, De Jonge, Janssen and Van Breukelen (1996) and Demerouti, Bakker, De Jonge, Janssen, & Schaufeli (2001) reported that job involvement varied positively with control; no main or interaction effects with job demands were found.…”
Section: Active Learning: What Do We Know?supporting
confidence: 55%
See 1 more Smart Citation
“…In the context of Karasek and Theorell's (1990) learning hypothesis, the highest levels of commitment/involvement are expected among incumbents of active jobs; the lowest levels are expected for passive jobs. Consistent with the active learning hypothesis, Landsbergis et al (1992) found that levels of job involvement were highest in active jobs. However, De Jonge, Janssen and Van Breukelen (1996) and Demerouti, Bakker, De Jonge, Janssen, & Schaufeli (2001) reported that job involvement varied positively with control; no main or interaction effects with job demands were found.…”
Section: Active Learning: What Do We Know?supporting
confidence: 55%
“…The results of two other studies are not entirely consistent with the learning hypothesis. Landsbergis, Schnall, Deitz, Friedman and Pickering (1992) reported that levels of job dissatisfaction were the lowest in low strain jobs (and not in active jobs), while Dollard and Winefield (1998) found that the highest levels of dis satisfaction occurred in high strain jobs (and not in passive jobs).…”
Section: Active Learning: What Do We Know?mentioning
confidence: 99%
“…Some studies have shown an association between neuroticism and development of angina pectoris, but not with MI (21). In the New York City blood pressure study, "trait anxiety", a widely used measure of negative affectivity (l18), was not correlated with work systolic (r = 0.01), work diastolic blood pressure (r = 0.00), or job strain (71,99).…”
Section: Personalitymentioning
confidence: 99%
“…However, the "active-passive" dimension of the model has been underutilized in organizational research (10). Only a few studies provide some evidence for the active-passive dimension of the model (11)(12)(13)(14). Studies measuring both strain and motivation or active learning find stronger support for the model than do those restricted to strain consequences (15).…”
mentioning
confidence: 99%